Sistem Informasi Pengajuan Cuti dan Izin Berbasis Web - Fatoni Fatoni; Dony Wahyu Isprananda; Ahmad Syazili (ISB Atma Luhur, 2020)
Bina Darma University is an educational institution that has the obligation to provide leave rights for its employees and lecturers. For the process of implementing, managing, calculating, replacing leave will be the task of the Directorate of Human Resources (DSDM). DSDM has provisions regarding rules for granting leave or permission not to work. Employees and lecturers who will apply for leave must submit the application in writing using the leave application form. The application of this manual method has several weaknesses, namely lack of efficiency, takes a long time because it has not been computerized. Also less effective in the work process, because of the many uses of paper so difficult to control the approval of the application especially if the applicant and the approver is not in the workplace location. Based on these conditions a system is needed to assist in the regulation of leave and permit applications for employees and lecturers. The method used in developing this system is the Rapid Application Development (RAD) method. There are three phases in RAD namely planning, design workshops and implementation.